Molecular evaluation of transovarial transmission of the Uruguayan vaccine strains of Babesia bovis and Babesia bigemina - Nel, Louis Hendrik (University of Pretoria, 2013)
Dissertation (MSc (Microbiology))--University of Pretoria, 2006.